Review of Enhanced Access Limits Under the Rapid Credit Facility and Rapid Financing Instrument. (Policy Papers; Policy Paper ;, 2020)
The temporary increase in access limits under IMF emergency financing instruments will expire on October 5, 2020, unless extended. Access limits under emergency instruments (the Rapid Credit Facility (RCF) and Rapid Financing Instrument (RFI)) were increased in April 2020 for a period of six months, from 50 to 100 percent of quota annually and from 100 to 150 percent of quota cumulatively. The increased limits are subject to review and can be extended before their expiration. It is proposed to extend the period of higher access limits for emergency financing for a period of six months, through April 6, 2021. Against a background of continued pandemic-related disruption, staff expects there could be significant demand for emergency lending in the October 2020-April 2021 period, including from countries with pending requests and from countries that received emergency support at levels less than the maximum amounts available. A six-month extension would give more time for countries to benefit from higher access limits under emergency financing.